Determinants of mental health and life satisfaction in Iranian older adults: a data-driven clustering study based on the biopsychosocial model - Asadollahi, Abdolrahim; Ahmad, Nobaya; Sokout, Tahereh; Abyad, Abdulrazzak (Intelektual Pustaka Media Utama, 2025)
The rapid growth of the global aging population, including in Iran, has intensified the need to understand the physical, psychological, and social challenges faced by older adults. Identifying key determinants of mental well-being and life satisfaction is essential for guiding policies that support healthy aging. This study examined demographic, socioeconomic, and health-related predictors of general health, assessed with the GHQ-28, and life satisfaction measured by the LSI among Iranian adults aged 60 years and older. A cross-sectional survey was conducted among 3,000 older adults using validated instruments (GHQ-28, LSI, and a structured questionnaire). Statistical analyses included descriptive statistics, ANOVA, multiple linear regression, and survival analysis. Reliability was confirmed with McDonald’s Omega values exceeding 0.87. Chronic diseases, pension status, daily life problems, and housing conditions emerged as significant predictors of both general health and life satisfaction. Women reported poorer general health than men, while married participants showed higher life satisfaction than those single or widowed. Chronic diseases were prevalent (75.7%) and associated with lower LSI scores. Economic insecurity, particularly the lack of pensions among women, was linked to worse GHQ scores. Survival analysis indicated that individuals with chronic disease had an 85% higher risk of experiencing daily problems (HR = 1.85). Socioeconomic and health factors substantially influence well-being in later life. Improving pension coverage, healthcare access, and social support systems may enhance healthy aging among Iranian older adults.